The impact of liquidity constraints on the effectiveness of fiscal policy: evidence from Poland - Krajewski, Piotr; Piłat, Katarzyna (Technological and Economic Development of Economy, 2025)
The aim of the paper is to estimate the impact of the rapid worsening of households’ access to credit in Poland on the effects of fiscal policy. The novelty of our study is that it extends the analysis of liquidity constrained households’ impact on fiscal multipliers to Central and Eastern European country, where households access to credit is relatively limited and therefore the potential impact of liquidity constrained households on fiscal multipliers is stronger than the existing literature for highly developed economies indicates. The empirical analysis is based on the theoretical model with heterogenous households. We found that the increase in the percentage of liquidity constrained households led to the substantial rise in fiscal multipliers, and thus the increase of effectiveness of Polish fiscal policy. The study indicates that before the worsening of households’ access to loans, the contemporaneous government spending multiplier was relatively low, whereas after a sharp increase in interest rates, contemporaneous government multiplier exceeded one. What is more, our study shows that a sharp increase in interest rates also strengthens medium term fiscal policy impact on GDP in Central and Eastern European economy. First published online 14 November 2024